Effect of one night of sleep deprivation on the diurnal patterns of steroid hormones - Labsy, Z.; Vibarel-Rebot, N.; Rieth, N.; Do, M.-C.; Gagey, O.; Zorgati, H.; Collomp, K. (Science & Sports, 2017)
The purpose of this investigation was to determine the effects of one night of sleep deprivation on the waking and diurnal cycles of cortisol, dehydroepiandrosterone (DHEA) and testosterone. Saliva samples were collected every 3 hours from 0600 to 2100 hours on 2 separate days [after 1 night of 8 hours in bed; after 1 night with complete sleep deprivation] in 9 recreationally trained soccer players. Diurnal decline for all steroids was observed under both conditions. There was, however, a significant increase in cortisol concentrations on the 2nd part of the day (i.e., 1800 and 2100 hours, P < 0.05) after sleep deprivation vs. the control night. The results of this investigation indicate that one night of sleep deprivation does not affect the circadian pattern of saliva adrenal and gonadal steroids in recreationally trained athletes over a 15-hour waking period, despite higher end-afternoon and evening cortisol levels. Further studies are needed to determine the potential impact of these increased catabolic hormone concentrations induced by one night of sleep deprivation on cognitive and physiological performance capacity involved in soccer match or training.